La dualidad en el poema "El Dios ibero" de Antonia Machado - Velasco Gómez Gutiérrez, Dolores (Acta Hispanica, 2015)
The Generation of ’98 was the name of a group of Spanish writers born between 1864 and 1875 whose common feature was the influence caused by the Hispanic crisis of 1898. Most of these authors tried to propose solutions through their writings. Antonio Machado’s poem “The Iberian God” was placed in this context. The poet, through a game of dualities, describes the unsettled God that determines the religiosity of the Hispanic man and suggests the god he yearns for, a firm and grim god, shaped by the Iberian man in a piece of Castilian oak, symbol of Spanish unity.